(untitled) (Global Scientific Review, 2024)
This study explores the multifaceted dynamics of teacher-student interaction and its influence on the process of English language learning. The interaction between teachers and students has long been acknowledged as a crucial determinant of educational outcomes, particularly in the context of language learning. This research delves into the various dimensions of teacher-student interaction, encompassing verbal and non-verbal communication, rapport building, feedback mechanisms, and motivational strategies. The impact of these interactions on the cognitive, affective, and social dimensions of English language learning is thoroughly examined. Furthermore, the study investigates the role of cultural and contextual factors in shaping teacher-student interactions and their implications for English language acquisition. Drawing on empirical evidence and existing theoretical frameworks, this research aims to shed light on the intricate relationship between teacher-student interaction and the enhancement of English language learning